Penguatan Karakter Toleran Siswa Melalui Pembelajaran Berbasis Nilai Kearifan Lokal dan Pancasila di Tanjung Dayang Selatan - Sukron Mazidi; Citra Lidiawati; Mita Purnama; Agnesia Veranica; Siti Nurhaliza (Journal of Civic Education, 2026)
This study aims to develop and evaluate the effectiveness of a local wisdom-based civic engagement learning model in South Tanjung Dayang to strengthen students' tolerance through the actualization of Pancasila values in response to increasing intolerance and the limited integration of local wisdom in Civic Education. This study employed a sequential explanatory mixed-methods design involving purposively selected Civic Education students at the Islamic University of Ogan Komering Ilir. Data were collected using tolerance questionnaires, observations, and semi-structured interviews. The results showed that the civic engagement learning model based on local wisdom significantly improved students' tolerance character (p < 0.05). Qualitatively, students showed improvements in aspects of respect for diversity, inclusive attitudes, participatory dialogue, and collective awareness based on the value of mutual cooperation. The actualization of Pancasila values, particularly the second and third principles, is internalized through collaborative activities with the Tanjung Dayang Selatan community, such as community meetings, community service, and cross-cultural forums. These findings confirm that the integration of local wisdom into participatory learning not only strengthens civic competence but also builds a character of tolerance in a contextual and sustainable manner. This study recommends the development of a Civic Education curriculum that is adaptive to the local context as a character-building strategy in higher education.